2022
DOI: 10.1016/j.clml.2021.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Oral Azacitidine (CC-486) for the Treatment of Myeloid Malignancies

Abstract: and Amgen. AHW is a former employee of the Walter and Eliza Hall Institute and receives a fraction of its royalty stream related to venetoclax. ILT, BS, and CLB: Employment and equity interest: Bristol Myers Squibb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 101 publications
(188 reference statements)
0
11
0
1
Order By: Relevance
“…CC-486 is an oral form of AZA, while ASTX727 is an oral decitabine analogue combined with cedazuridine -the cytidine deaminase inhibitor. They are characterized by other, more convenient methods of administration and give more comfort to the patient due to fewer visits and time at the hospital [36,41].…”
Section: Hypomethylating Drugsmentioning
confidence: 99%
“…CC-486 is an oral form of AZA, while ASTX727 is an oral decitabine analogue combined with cedazuridine -the cytidine deaminase inhibitor. They are characterized by other, more convenient methods of administration and give more comfort to the patient due to fewer visits and time at the hospital [36,41].…”
Section: Hypomethylating Drugsmentioning
confidence: 99%
“…The oral formulation of azacitidine allows a prolonged schedule of administration, which consequently extends the exposure of AML cells to the drug, sparing inconveniences related to injections and promoting a particular hypomethylating profile and weaker cytotoxic effects [ 164 , 165 , 166 , 167 ].…”
Section: New Formulations Old Drugsmentioning
confidence: 99%
“…A total of 236 patients were taken into consideration and were given 300 mg for 14 days to treat AML. The frequencies of thrombocytopenia, anemia, and neutropenia were 33%, 20%, and 44%, respectively [159]. The toxic effect of azacitidine was also evaluated in another cohort of MDS patients.…”
Section: Hematological Toxicities Of Anticancer Nucleoside Drugsmentioning
confidence: 99%
“…A total of 107 patients were taken into consideration: 300 mg/day was given to them for 21 days and the side effects were analyzed. Of these 107 patients, 20 were affected by anemia, 31 by thrombocytopenia, and 50 by neutropenia [159,160]. The frequency ranges of various hematological toxicities observed in various studies are shown in Table 2.…”
Section: Hematological Toxicities Of Anticancer Nucleoside Drugsmentioning
confidence: 99%